The Potential of RICOSRE's Learning Model in Improving Cognitive Learning Outcomes - Irma Dahlia Yuliskurniawati; Susriyati Mahanal; Siti Zubaidah; Abdul Gofur (Universitas Negeri Malang, 2019)
Abstract: Cognitive learning outcomes are learning outcomes that focus on intellectual knowledge. Some researches showed that the students learning outcomes of high school in Malang were still need improved. The study aims to determine the effect of the RICOSRE learning model in improving students' cognitive learning outcomes. This type of research is quasi experiment, using students of SMAN 1 Malang, SMAN 8 Malang, SMAN 1 Turen, and SMAN 1 Singosari as participants. Data analysis used covariance analysis then followed by post hoc test of LSD. The results of the analysis show that the RICOSRE learning model can improve students' cognitive learning outcomes compared to learning using Problem Based Learning and conventional learning. Key Words: cognitive learning outcomes, RICOSRE learning model Abstrak: Hasil belajar kognitif merupakan pencapaian belajar yang berada pada domain yang berfokus pada pengetahuan dan keahlian intelektual. Berbagai hasil penelitian menunjukkan bahwa secara umum hasil belajar siswa SMA di Malang masih perlu ditingkatkan. Penelitian bertujuan untuk mengetahui pengaruh model pembelajaran RICOSRE dalam meningkatkan hasil belajar kognitif siswa di Malang, Jawa Timur. Jenis penelitian adalah kuasi eksperimen, dengan menggunakan partisipan siswa di SMAN 1 Malang, SMAN 8 Malang SMAN 1 Turen, dan SMAN 1 Singosari. Analisis data menggunakan analisis kovarian kemudian dilanjutkan uji lanjut LSD. Hasil analisis data menunjukkan model pembelajaran RICOSRE dapat meningkatkan hasil belajar kognitif siswa dibandingkan pembelajaran menggunakan Problem Based Learning dan pembelajaran konvensional. Kata kunci: hasil belajar kognitif, model pembelajaran RICOSRE